2017
DOI: 10.1159/000462979
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Treatment of Hidradenitis Suppurativa: A Review

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease presenting with painful nodules, abscesses, sinus tracts, and scarring primarily affecting apocrine gland-rich intertriginous areas. HS prevalence ranges from 0.05 to 1%. The central pathogenic event in HS is believed to be the occlusion of the upper part of the folliculopilosebaceous unit, leading to the rupture of the sebofollicular canal with the consequent development of perifollicular lymphohistiocytic inflammation. The HS treatment choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 153 publications
(189 reference statements)
1
67
0
12
Order By: Relevance
“…Therefore, it may not capture the widely variable clinical presentation of HS. Furthermore, it possesses limited value for monitoring the efficacy of medical and surgical interventions . Given our findings, the number of body sites may have increased utility over Hurley grading when assessing the risk of recurrence post‐excisional surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it may not capture the widely variable clinical presentation of HS. Furthermore, it possesses limited value for monitoring the efficacy of medical and surgical interventions . Given our findings, the number of body sites may have increased utility over Hurley grading when assessing the risk of recurrence post‐excisional surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Although recent studies have shown that monoclonal antibodies against TNF- α are effective in moderate to severe HS, none of our patients had yet to receive biologic treatment [ 28 ]. This is due to our limited financial resources in this fully funded government clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reconstructive modalities after surgical excision have been described, including primary closure, healing by secondary intent, split-thickness skin graft (STSG), and flap closure [16]. Scuderi et al [17] recently reviewed several surgical and reconstructive techniques for HS. Despite the many surgical and reconstructive techniques available, there is still no general consensus on the preferred surgical technique [18,19] (Table 1).…”
Section: Reconstructive Techniquesmentioning
confidence: 99%